Problems before Chief Justice Gordon Sloan - Banerji, J. (Indian Forester, 1955)
The Forest Management Licence System of British Columbia (Canada), in which exploitation and regeneration of extensive forest tracts are left in the hands of large industrialists for considerable periods at a time, will currently stand a critical analysis by the Hon'ble Chief Justice Gordon McG. Sloan, who has now been appointed to review the forestry practices of the State. This system has recently attracted considerable attraction due to some of the licensees stating that it gives the Government almost life-and-death power over the industrialists. Small Saw-millers also have complained about their inability to procure raw materials for their industries. Principles of long-term leases in India, specially in Assam, Bombay, Uttar Pradesh and Andamans, have been examined. In some under-developed countries Governments participate in the development of industries; current cases from New Zealand, Bristish Guiana, Nigeria, and New Guinea have been cited. It appears that regeneration is usually done by the Government; logging may, or may not, be left with the long-term licensee; an impartial assessment of annual revenue to be paid to the Government by the licensee is difficult, but satisfactory solutions are possible if certain principles are observed.